Pengaruh Carbon Performance Awareness, Ethical Accounting Behavior, dan Green Decision-Making Style terhadap Kualitas Pelaporan Keberlanjutan Perusahaan - Kurnadi Kurnadi; Effendy Gunardi; Amiartuti Kusmaningtyas; Maria Yovita R Pandin (SENTRI: Jurnal Riset Ilmiah, 2025)
Today's business world is navigating escalating social and environmental challenges. This situation is marked by the climate crisis, which is increasingly pressing global concerns. This event has become the root of movements to encourage critical thinking to address environmental and social crises. Global companies have begun publishing sustainability reports as a form of concern for the ongoing environmental crisis. This study attempts to examine the influence of carbon performance awareness, ethical accounting behavior, and green decision-making style on the quality of corporate sustainability reporting. The results of this study found that carbon performance awareness and green decision-making style influence the quality of corporate sustainability reporting. The findings of this study indicate that awareness of carbon emissions, supported by a sustainable decision-making style, can influence the quality of corporate sustainability reporting.